Plasmonic self-assembly of pH-responsive gold-nanocomposite at polar/non-polar solvents interface - Kemas Aurino Muhammad. (2011)
Previous reports on self-assembly of AuNP have encouraged us to do experimentation on a synthesis of an AuNP-polymer composite which is able to self-assemble in response to pH change. In this project, we tailored the AuNP, which is previously modified with PEG (poly ethylene glycol) via “grafting to” technique, with 4VP (4-vinyl pyridine)-DEAEMA (diethyl aminoethyl methacrylate) copolymer brush, creating AuNP@PEG-poly(4VP-co-DEAEMA) composite. The attachment of the copolymer brushes to the AuNP surface was carried out via SI-ATRP (surface-initiated atomic transfer radical polymerization) technique, using DTBE as an initiator to initiate the whole polymerization process. In later step, CuBr and Me6Tren were introduced to the reaction vessel as catalyst and ligand, respectively. The pH-sensitivity of both 4VP and DEAEMA in the copolymer chains provides a mean to self-assemble the AuNP@PEG-poly(4VP-co-DEAEMA) composite by changing the solvent quality and pH. It was shown that the self-assembly was triggered by increasing the hydronium ion concentration in the solution until pH = 8.0 and the assembled-layer formation is reversible. Such self-assembly has a wide potential, such as in application involving formation of nanostructure from nanoscale building blocks, including nanometric sensors.